Image Improvement Using The Combination of Wavelet and Multiwavelet Transform - AL-Khafaji, B.J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This paper introduces method of image enhancement using the combination of both wavelet and Multiwavelet transformation. New technique is proposed for image enhancement using one smoothing filter.    A critically- Sampled Scheme of preprocessing method is used for computing the Multiwavelet.It is the 2nd norm approximation used to speed the procedures needed for such computation.  An improvement was achieved with the proposed method in comparison with the conventional method.  The performance of this technique has been done by computer using Visual Baisec.6 package.